Epidermal Stem Cells in Wound Healing and Regeneration - Ronghua Yang; Jingru Wang; Xiaodong Chen; Yan Shi; Julin Xie (Stem Cells International)
Skin stem cells distributed in the basal layer of the epidermis and hair follicles are important cell sources for skin development, metabolism, and injury repair. At present, great progress has been made in the study of epidermal stem cells at the cellular and molecular levels. Stem cell transplantation is reported to promote skin healing, endothelial cell transformation, and vascular formation. Local stem cells can also be transformed into keratinocytes, sebaceous gland, and other skin-associated tissues. However, the mechanism of action of epidermal stem cells on wound healing and regeneration is not completely clear. This review is aimed at briefly summarizing the biological characteristics of epidermal stem cells and their clinical application in wound healing and tissue regeneration. It further discussed the mechanism of action and the development direction in the future.